Transforming Human Resource Management Strategies to Address the Quiet Quitting Phenomenon Through a Contemporary Literature Review Approach - Soni Wirawan; Raden Andi Sularso; Julio Norberto (Mandalika Institute, 2026)
The emergence of quiet quitting has become a significant challenge for contemporary organizations, reflecting employees' psychological disengagement despite maintaining formal employment. This study aims to examine how Human Resource Management (HRM) strategies can be transformed to address the quiet quitting phenomenon through a contemporary literature review approach. The research employs library research using relevant scholarly publications as primary data and supporting literature as secondary data. Data were collected through systematic literature review and analyzed using content analysis to identify patterns, relationships, and strategic insights. The findings indicate that traditional HRM practices are insufficient to address evolving employee expectations in modern workplaces. Contemporary HRM strategies emphasizing employee engagement, transformational leadership, career development, organizational support, workplace well-being, and flexible work arrangements are more effective in reducing quiet quitting behavior. The study concludes that employee-centered HRM transformation strengthens organizational commitment, enhances employee engagement, and contributes to sustainable organizational performance. These findings provide both theoretical contributions to contemporary HRM literature and practical recommendations for organizations seeking to mitigate employee disengagement.